Use of Tablet Computers to Promote Physical Therapy Students' Engagement in Knowledge Translation During Clinical Experiences. Issue 2 (April 2016) - Tilson, Julie K.; Loeb, Kathryn; Barbosa, Sabrina; Jiang, Fei; Lee, Karin T.
Abstract : Background and Purpose: Physical therapists strive to integrate research into daily practice. The tablet computer is a potentially transformational tool for accessing information within the clinical practice environment. The purpose of this study was to measure and describe patterns of tablet computer use among physical therapy students during clinical rotation experiences. Methods: Doctor of physical therapy students (n = 13 users) tracked their use of tablet computers (iPad), loaded with commercially available apps, during 16 clinical experiences (6-16 weeks in duration). Results: The tablets were used on 70% of 691 clinic days, averaging 1.3 uses per day. Information seeking represented 48% of uses; 33% of those were foreground searches for research articles and syntheses and 66% were for background medical information. Other common uses included patient education (19%), medical record documentation (13%), and professional communication (9%). The most frequently used app was Safari, the preloaded web browser (representing 281 [36.5%] incidents of use). Users accessed 56 total apps to support clinical practice. Discussion and Conclusions: Physical therapy students successfully integrated use of a tablet computer into their clinical experiences including regular activities of information seeking. Our findings suggest that the tablet computer represents a potentially transformational tool for promoting knowledge translation in the clinical practice environment. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A127 ). Abstract : Supplemental Digital Content is Available in the Text.